ANALISIS PENGUKURAN KERJA DALAM MENENTUKAN WAKTU STANDAR PADA OPERATOR MESIN CNC DI PT TEAM METAL INDONESIA - Pamungkas, Doni; Zetli, Sri (Computer Science and Industrial Engineering, 2023)
PT Team Metal Indonesia is a company located in Bintang Industrial Park II Area, Tanjung Uncang, Batam City. Many targets cannot be met by operators and a lot of idle time is caused by the absence of time standards set by the company. This study aims to determine the standard time needed by CNC machine operators to complete each job and to determine the productivity of CNC machine operators. The data collection method in this study is primary data obtained directly from measurements carried out at the production site using stopwacth. While the data analysis method uses the stopwach time study method. The results of the study calculated the raw time of making 1 pcs is 1470,325 seconds. The standard time per work element for Material Installation is 150.7037 seconds, the Chip Cleaning and Tool checking process produces a standard time of 19.05648 seconds and Material Opening is 128.5649 seconds, and for the output produced by the operator in one shift can be produced as much as 14-16 pcs in one shift before the standard time is determined, and can be produced as many as 17 pcs in one shift after the standard time is set.